Strategi Adaptasi Mahasiswa Perantauan Jombang di Kota Surabaya - Syafi'i, Imam; Sadewo, Fransiscus Xaverius Sri (Paradigma, 2023)
The difference of culture between the society of Jombang and Surabaya has caused cultural shock for students from Jombang who continue their education at colleges and universities in Surabaya. Thus, in facing the presence of new cultures and customs in their surroundings, these students from Jombang require adaptation strategies to adjust to their new environment and sustain their livelihoods. This research aims to identify the socio-cultural backgrounds, efforts to meet their needs, challenges faced, and analyze the adaptation strategies employed by these students from Jombang in Surabaya. The study employs qualitative research methods with an ethnomethodological approach by Harold Garfinkel. Data analysis is based on Lazarus and Folkman's coping strategies theory, which consists of emotion-focused coping and problem- focused coping aspects. The research findings reveal that the students from Jombang employ emotion-focused coping strategies when dealing with stress, by controlling their emotional state through prayer to God, seeking alternative activities like phone calls or video calls with their parents, coffee gatherings, refreshing activities, smoking, and playing online games. On the other hand, when utilizing problem-focused coping strategies, these students from Jombang take action or seek solutions by expanding their social networks through making friends with senior students, forming study groups, seeking help from friends, and participating in organizations. Keywords: Migrant Students; Culture Shock; Adaptation; Coping Strategies